(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The debatable questions of lyrics genre nature are investigated in the article, lyrics genelogical conceptions, developed by the literary critics of ХХ century are systematized and summarized. Addressed lyrics is considered as the genre formation which includes poetic genres with underlined addressed direction, in other words, the genres where communication with the internal text addressee appears as the subject of image. The genre forms of addressed lyrics (message, dedication and a letter, written in verse), their typology and theory of poetry are analysed.